2018
DOI: 10.1002/jcb.27352
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of IL‐17A, IL‐17F, IL‐23R, VDR, CCL2, CCL5, CCR2, and CCR5 gene polymorphisms and expression in Chinese individuals with syphilis

Abstract: Syphilis is a sexually transmitted disease caused by the infection of Treponema pallidum subspecies pallidum. T-helper type 17-related genes, vitamin D receptor (VDR) gene, and chemokine/chemokine receptor genes are crucial in microbial infection. A total of 16 single-nucleotide polymorphisms (SNPs) in eight genes (interleukin [IL]-17A, IL-17F, IL-23R, VDR, C-C motif chemokine ligand [CCL] 2, CCL5, C-C chemokine receptor [CCR] 2, and CCR5) were analyzed in 188 patients with syphilis and 216 healthy controls. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Hu et al 21 analyzed single-nucleotide polymorphisms (SNPs) in genes for 8 cytokines in 188 Chinese individuals with syphilis (77 of whom had early syphilis) and 216 healthy controls in a case-control study. No significant correlation was found between the levels of IL-17 mRNA and IL-17 secretion in plasma and T. pallidum infection.…”
Section: Resultsmentioning
confidence: 99%
“…Hu et al 21 analyzed single-nucleotide polymorphisms (SNPs) in genes for 8 cytokines in 188 Chinese individuals with syphilis (77 of whom had early syphilis) and 216 healthy controls in a case-control study. No significant correlation was found between the levels of IL-17 mRNA and IL-17 secretion in plasma and T. pallidum infection.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, Wang and coworkers reported an HIV patient who had two episodes of UNRS, separated by 13 months, despite receiving ART after the first episode [ 19 ]. Thus, these two patients, despite improving CD4 counts and suppression of HIV viral load, had another unknown immunologic predisposition to develop UNRS, such as a specific genetic polymorphism that affects the expression of particular cytokines, chemokines, or their receptors [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the researchers also investigated whether IL17A rs2275913 and rs3819024 were linked to IL17A mRNA expression and secretion in syphilis patients. Therefore, it was confirmed that the IL17A polymorphisms rs2275913 and rs3819024, as well as the haplotype including these two SNPs, influenced syphilis susceptibility (15). Not much research has been conducted on the association of host genes with syphilis and this calls for more investigations.…”
Section: Host Genetic Factors Associated With Treponema Pallidum Infe...mentioning
confidence: 93%
“…The findings showed a significant correlation of IL-17 A rs2275913 (AA vs. AG + GG) and rs3819024 (GG vs. AA + GA) for those with syphilis. The IL-17 A rs2275913A/rs3819024G haplotype showed a risk effect in haplotype analysis, while IL-17 A rs2275913G/rs3819024A showed a protective effect ( 15 ).…”
Section: Host Factors Associated With Sexually Transmitted Infectionsmentioning
confidence: 99%